Meniscus Root Repair vs Meniscectomy or Nonoperative Management to Prevent Knee Osteoarthritis After Medial Meniscus Root Tears: Clinical and Economic Effectiveness. Issue 3 (March 2019) - Faucett, Scott C.; Geisler, Benjamin Peter; Chahla, Jorge; Krych, Aaron J.; Kurzweil, Peter R.; Garner, Abigail M.; Liu, Shan; LaPrade, Robert F.; Pietzsch, Jan B.
Background: Medial meniscus root tears are a common knee injury and can lead to accelerated osteoarthritis, which might ultimately result in a total knee replacement. Purpose: To compare meniscus repair, meniscectomy, and nonoperative treatment approaches among middle-aged patients in terms of osteoarthritis development, total knee replacement rates (clinical effectiveness), and cost-effectiveness. Study Design: Meta-analysis and cost-effectiveness analysis. Methods: A systematic literature search was conducted. Progression to osteoarthritis was pooled and meta-analyzed. A Markov model projected strategy-specific costs and disutilities in a cohort of 55-year-old patients presenting with a meniscus root tear without osteoarthritis at baseline. Failure rates of repair and meniscectomy procedures and disutilities associated with osteoarthritis, total knee replacement, and revision total knee replacement were accounted for. Utilities, costs, and event rates were based on literature and public databases. Analyses considered a time frame between 5 years and lifetime and explored the effects of parameter uncertainty. Results: Over 10 years, meniscus repair, meniscectomy, and nonoperative treatment led to 53.0%, 99.3%, and 95.1% rates of osteoarthritis and 33.5%, 51.5%, and 45.5% rates of total knee replacement, respectively. Meta-analysis confirmed lower osteoarthritis and total knee replacement rates for meniscus repair versus meniscectomy and nonoperative treatment. Discounted 10-year costs were 22, 590 for meniscus repair, as opposed to 31, 528 and 25, 006 for meniscectomy and nonoperative treatment, respectively; projected quality-adjusted life years were 6.892, 6.533, and 6.693, respectively, yielding meniscus repair to be an economically dominant strategy. Repair was either cost-effective or dominant when compared with meniscectomy and nonoperative treatment across a broad range of assumptions starting from 5 years after surgery. Conclusion: Repair of medial meniscus root tears, as compared with total meniscectomy and nonsurgical treatment, leads to less osteoarthritis and is a cost-saving intervention. While small confirmatory randomized clinical head-to-head trials are warranted, the presented evidence seems to point relatively clearly toward adopting meniscus repair as the preferred initial intervention for medial meniscus root tears.